2005
DOI: 10.2166/wst.2005.0626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-coagulation on mitigating irreversible fouling during ultrafiltration of a surface water

Abstract: Membrane fouling can be divided into two types: reversible fouling and irreversible fouling. The former can be easily canceled by physical cleaning (e.g., backwashing) while the latter needs chemical cleaning to be mitigated. For more efficient use of membranes, the control of irreversible membrane fouling is of importance. In this study, the effectiveness of pre-coagulation/sedimentation on irreversible membrane fouling was investigated, based on the pilot-scale operation of the membrane unit installed at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…However, membrane fouling, primarily caused by natural organic matter (NOM), severely limits the efficient operation of large-scale industrial systems by increasing operational costs and hydraulic resistance (Peiris et al, 2008). Several pre-treatment methods have been implemented to mitigate membrane fouling in drinking water treatment including coagulation (Kimura et al, 2005), flocculation (Wang et al, 2013), oxidation (Mozia et al, 2006), and bio-filtration (Peldszus et al, 2012). Most of these methods transfer organic matter and pollutants from the aqueous phase to a solid phase necessitating subsequent treatment of the solid phase (Huck and Sozań ski, 2008;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, membrane fouling, primarily caused by natural organic matter (NOM), severely limits the efficient operation of large-scale industrial systems by increasing operational costs and hydraulic resistance (Peiris et al, 2008). Several pre-treatment methods have been implemented to mitigate membrane fouling in drinking water treatment including coagulation (Kimura et al, 2005), flocculation (Wang et al, 2013), oxidation (Mozia et al, 2006), and bio-filtration (Peldszus et al, 2012). Most of these methods transfer organic matter and pollutants from the aqueous phase to a solid phase necessitating subsequent treatment of the solid phase (Huck and Sozań ski, 2008;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is now very common to use coagulation as pretreatment of microfiltration (MF) and ultrafiltration (UF) to increase the removal of natural organic matter [1], improving membrane flux and even mitigate irreversible membrane fouling [2]. The hybrid coagulation-microfiltration process such as submerged membrane systems or direct membrane filtration processes which do not require to include settling processes are becoming more popular in the water industry [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pikkarainen et al [39] found that pre-coagulation enhanced the DOC removal in upland surface water by more than 80% in a coagulation-assisted MF process. In our coagulation/dead-end MF process, on the other hand, the highest removal of DOC and UV 254 was 68% and 72%, respectively, which could be explained by the much lower SUVA value of the DOM [40]. As shown in Table 1, the SUVA value of SFBW was about 1.4 (less than 2), suggesting that the DOM in SFBW are low molecular weight and low hydrophobicity.…”
Section: Effect Of Coagulation Mechanism On Membrane Filtrationmentioning
confidence: 68%